Curricular proposal for teaching catholic religion and promotion of climate change - Fernández-Morilla, Mónica; Albareda-Tiana, Silvia; Fuertes-Camacho, Mª Teresa; Graell-Martín, Mariona; Jiménez-López, Esther (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Since the publication of Pope Francis’ encyclical Laudato si’ (LS) in 2015, multiple actions have been taken to foster a comprehensive vision of ecology in the Catholic Church. The objective was the development of a curricular proposal that includes sustainable and holistic development in the teaching of the Catholic religion. The CHANCES course offers a new paradigm for the teaching of the Catholic religion, showing how from it, deep motivations can be discovered, and attitudes and virtues can be promoted, which can contribute to the development of competences in sustainability.